1962
DOI: 10.1161/01.cir.26.6.1235
|View full text |Cite
|
Sign up to set email alerts
|

Supravalvular Aortic Stenosis in Association with Mental Retardation and a Certain Facial Appearance

Abstract: Four patients with supravalvular aortic stenosis are reported. In three of these patients a certain facial resemblance was striking, and these three patients were also mentally and physically retarded. The cases are very similar to the four cases recently reported in the literature. Supravalvular aortic stenosis in association with mental retardation and a certain facial appearance may constitute a previously unrecognized clinical syndrome. A systolic thrill and murmur most pronounced in the first ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
184
0
12

Year Published

1964
1964
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(200 citation statements)
references
References 15 publications
(1 reference statement)
4
184
0
12
Order By: Relevance
“…We demonstrated a direct relationship between impaired elastogenesis and heightened proliferation of human aortic SMCs derived from patients with supravalvular aortic stenosis and Williams-Beuren syndrome, 80 both of which are characterized by haploinsufficiency of the elastin gene and by development of arterial occlusions. 81,82 We also reported the association between impaired elastogenesis and heightened cellular proliferation in a mechanism leading to the development of hypertrophic cardiopathy and arterial occlusions in Hurler's disease and Costello syndrome. 63, 64 We further found that insoluble elastin is capable of sequestering certain mitogenic growth factors, including PDGF 28 and that heightened proliferation of cultured arterial SMCs and fibroblasts from patients with supravalvular aortic stenosis and Williams-Beuren syndrome could be reversed by the addition of exogenous insoluble elastin.…”
Section: Figure 5 Results Of [mentioning
confidence: 90%
“…We demonstrated a direct relationship between impaired elastogenesis and heightened proliferation of human aortic SMCs derived from patients with supravalvular aortic stenosis and Williams-Beuren syndrome, 80 both of which are characterized by haploinsufficiency of the elastin gene and by development of arterial occlusions. 81,82 We also reported the association between impaired elastogenesis and heightened cellular proliferation in a mechanism leading to the development of hypertrophic cardiopathy and arterial occlusions in Hurler's disease and Costello syndrome. 63, 64 We further found that insoluble elastin is capable of sequestering certain mitogenic growth factors, including PDGF 28 and that heightened proliferation of cultured arterial SMCs and fibroblasts from patients with supravalvular aortic stenosis and Williams-Beuren syndrome could be reversed by the addition of exogenous insoluble elastin.…”
Section: Figure 5 Results Of [mentioning
confidence: 90%
“…Williams syndrome (WS) is a well defined developmental disorder that is characterized by distinctive facial features, growth deficiency, mental retardation, a gregarious personality, congenital heart defects (particularly supravalvular aortic stenosis [SVAS] with or without peripheral pulmonary stenosis), and hypercalcemia of early infancy (Williams et al 1961, Beuren et al 1962, Morris et al 1988. Generally, seizures are not associated with WS.…”
Section: Introductionmentioning
confidence: 99%
“…It gives rise to specific physical, behavioural and cognitive abnormalities, page 10 together with structural, chemical and functional anomalies in the developing brain (Bellugi, Wang & Jernigan, 1994;Grice et al, 2001;Mervis, Morris, Bertrand & Robinson, 1999;Rae, Karmiloff-Smith, Lee, Dixon, Grant, Blamire, Thompson, Styles & Radda, 1998). The syndrome was initially reported by cardiologists (Beuren, Apitz & Harmjanz, 1962;Williams, Barratt-Boyes & Lowe, 1961) (Black & Bonham-Carter, 1963). …”
Section: A Specific Example: Williams Syndromementioning
confidence: 99%